The influence of ball carriage on change of direction speed in male club-level lacrosse players - Rose, P. W.; Warne, J. P. (International Journal of Performance Analysis in Sport, 2024)
This study aimed to determine the effects of ball carriage on change of direction speed in club-level male lacrosse players using an L-run test when compared with two control conditions "no-ball, with-stick" and "no-ball, no-stick". Thirteen participants (M±SD; age = 27 ± 7.5 years; height = 179.5 ± 5.8 cm; body mass = 82.9 ± 11.3 kg) conducted a randomised, counterbalanced study. Each completed six trials, performing two repetitions under three conditions: "no-ball, no-stick" (NBNS), "no-ball, with-stick" (NBWS), and "with-ball, with-stick" (WBWS). L-run completion times were not different between NBWS (6.30 ± 0.25 s) and WBWS (6.38 ± 0.28 s) (p = 0.452, Mdiff = 0.07 s, 95% CIdiff [-0.06 to 0.20 s]). There was also no difference from the NBNS (6.22 ± 0.26 s) to the NBWS conditions (p = 0.095, Mdiff = 0.09 s, 95% CIdiff [-0.01 to 0.18 s]). However, completion time was significantly longer in the WBWS condition compared to the NBNS condition (p = 0.029, Mdiff = 0.16 s, 95% CIdiff [0.02 to 0.30 s]). Therefore, carrying a ball in a stick may negatively influence change of direction compared to with no ball or stick. Coaches should implement the lacrosse stick and cradling to better replicate the sport-specific mechanical demands of match-play.